Guidelines for sedation in gastroenterological endoscopy (second edition). Issue 1 (9th December 2020) - Gotoda, Takuji; Akamatsu, Takuji; Abe, Seiichiro; Shimatani, Masaaki; Nakai, Yousuke; Hatta, Waku; Hosoe, Naoki; Miura, Yoshimasa; Miyahara, Ryoji; Yamaguchi, Daisuke; Yoshida, Naohisa; Kawaguchi, Yosuke; et al.
Abstract : Sedation in gastroenterological endoscopy has become an important medical option in routine clinical care. Here, the Japan Gastroenterological Endoscopy Society and the Japanese Society of Anesthesiologists together provide the revised "Guidelines for sedation in gastroenterological endoscopy" as a second edition to address on‐site clinical questions and issues raised for safe examination and treatment using sedated endoscopy. Twenty clinical questions were determined and the strength of recommendation and evidence quality (strength) were expressed according to the "MINDS Manual for Guideline Development 2017." We were able to release up‐to‐date statements related to clinical questions and current issues relevant to sedation in gastroenterological endoscopy (henceforth, "endoscopy"). There are few reports from Japan in this field (e.g., meta‐analyses), and many aspects have been based only on a specialist consensus. In the current scenario, benzodiazepine drugs primarily used for sedation during gastroenterological endoscopy are not approved by national health insurance in Japan, and investigations regarding expense‐related disadvantages have not been conducted. Furthermore, including the perspective of beneficiaries (i.e., patients and citizens) during the creation of clinical guidelines should be considered. These guidelines are standardized based on up‐to‐date evidence quality (strength) and supports on‐site clinical decision‐making by patients and medical staff. Therefore, these guidelines need to be flexible with regard to the wishes, age, complications, and social conditions of the patient, as well as the conditions of the facility and discretion of the physician.